Association between asthma and dry eye disease: a meta-analysis based on observational studies - Jing Wang; Juan Wang; Chuantao Zhang; Qun Huang; Yanlin Zheng; Wanjie Wang; Tingting Liao; Xili Xiao (BMJ Open)
Objective This study aimed to systematically review the relationship between dry eye disease (DED) and asthma based on published population-based studies.Data sources PubMed, EMBASE and ISI Web of Science from their inception were searched up to October 2019.Study selection Observational studies addressing the association between asthma and DED will be eligible.Data extraction and synthesis Two reviewers independently conducted the data extraction and quality assessment. We used a random-effects model for all analyses. Subgroup analysis according to ethnicity was performed to test the influence of ethnicity on the association.Main outcomes and measures Six independent studies (a total of 45 215 patients with asthma and 232 864 control subjects) were included in this review and had an average of seven stars by the Newcastle-Ottawa Scale. Our current findings suggest that the prevalence of DED was higher in the asthma group than in the control group (Z=7.42, p<0.00001; OR 1.29, 95% CI 1.20 to 1.38). In the subgroup analysis by ethnicity, Australian, Caucasian and Asian patients with asthma showed an increased risk of DED.